2001
DOI: 10.1098/rspb.2001.1762
|View full text |Cite
|
Sign up to set email alerts
|

Genetic consequences of population decline in the European otter (Lutra lutra): an assessment of microsatellite DNA variation in Danish otters from 1883 to 1993

Abstract: The European otter (Lutra lutra) was common in Denmark until the 1960s, but its present distribution encompasses only a minor part of the country. The aim of this study was to assess whether the recent population decline has resulted in loss of genetic variability and to gain further insight into the dynamics of the population decline. This was done by analysing microsatellite DNA variation in contemporary and historical samples, the latter encompassing DNA samples extracted from museum specimens covering a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 24 publications
11
82
1
2
Order By: Relevance
“…Such 'ghost alleles' have subsequently been reported in several bottlenecked animal populations. By contrast, other studies have reported stable genetic diversity despite declines in population size [24][25][26]. For example, no obvious loss of genetic diversity was detected among Canadian peregrine falcons (Falco peregrinus) despite a DDT induced bottleneck [25].…”
Section: Nhc Samples In Conservation Geneticsmentioning
confidence: 40%
“…Such 'ghost alleles' have subsequently been reported in several bottlenecked animal populations. By contrast, other studies have reported stable genetic diversity despite declines in population size [24][25][26]. For example, no obvious loss of genetic diversity was detected among Canadian peregrine falcons (Falco peregrinus) despite a DDT induced bottleneck [25].…”
Section: Nhc Samples In Conservation Geneticsmentioning
confidence: 40%
“…To date, relatively few studies of wild populations have examined the loss of genetic variation over the course of a population decline or recovery. In some populations there has been a significant loss of both genetic variation and fitness (Westemeier et al 1998), but in other cases the results are less clear, as the genetic changes have been relatively small (Miller and Waits 2003), the loss of genetic variation predated the population decline (Mundy et al 1997;Pertoldi et al 2001) or the loss of genetic variation was associated with relatively minor effects on fitness (Weber et al 2000;Groombridge et al 2000, Bellinger et al 2003. To date, only two studies of populations in the wild have demonstrated a positive association between genetic variation and the risk of population extinction (Newman and Pilson 1997;Saccheri et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…New tools based on Bayesian statistics and coalescence theory are now available (Beaumont 1999;Pertoldi et al 2001;Storz & Beaumont 2002) to determine these from genetic data. Here, we used the procedure of Beaumont (1999) to detect population declines and expansions.…”
Section: (B) Panmixia In the American Eelmentioning
confidence: 99%